Technology use and digital learning characteristics among malaysian undergraduates - Hong, Kian-Sam; Norazila, Abdul Aziz (UTM Press., 2014)
Digital natives, the net generation or millennial generation are among the labels used to describe the characteristics of learners who are now in universities. They are assumed to be proficient in and use a wide range of digital technologies. In addition, they were posited to have different learning preferences. A number of studies have been carried out to determine and describe their knowledge, skills, understanding and purposes of using technologies. However, some researchers have begun to question some of the claims made about this group regarding their ability to use technology especially for learning purposes. Research and information on this group of learners in the Malaysian and Asian context regarding their use of technology and learning needs are limited. This paper reports a study that investigated the technology use and digital learning characteristics of undergraduates at a Malaysian public university. The cross sectional survey involved a random sample of 1059 undergraduates at the university. The results of the study showed that the students made use of digital technologies for their social activities and academic work. They regularly made use of a number of digital tools such as the mobile phone, laptop computer, Internet websites, Google, and Facebook/ MySpace both for their social activities and learning purposes. They perceive the digital tools used in their daily life to be useful for formal learning. They also appeared to have learning preferences similar to those posited for digital natives. These findings suggest a need for universities to further explore ways to harness common and applicable digital technologies to enhance students’ learning. In general, these findings further point to a need for higher education environments in Malaysia to evaluate their capacity to facilitate the learning needs of the technology-driven and multi-sensory new generation of students. It is suggested that further studies be undertaken to validate the findings of the present study and explicate reasons for students’ preferred use of digital technologies for formal and informal learning